Effectiveness of Multiple Mini Interviews in medical school admissions: assessment using The Big Five Personality framework - João Sampaio Góes; Stefano Ivani de Paula; Durval Aníbal Daniel-Filho; Elda Maria Stafuzza Gonçalves Pires; Ângela Tavares Paes; Eduardo Juan Troster (Einstein (São Paulo))
ABSTRACT Objective To evaluate the effectiveness of Multiple Mini Interviews as a selection method for medical school admissions at the Faculdade Israelita de Ciências da Saúde Albert Einstein by evaluating the relationship between the Big Five personality traits and the performance of candidates in the Multiple Mini Interviews. Methods All candidates who had completed the NEO PI-R personality test and the socio-demographic questionnaire were the participants of the study. The personality profiles of candidates who participated in the Multiple Mini Interviews process of this cross-sectional descriptive study were analyzed by crossing data to identify significant correlations. Results Of the 225 candidates, 63% were female and the mean age of the sample was 21 years. Only the domain of Conscientiousness showed significant correlations with higher Multiple Mini Interviews scores (p=0.004). Specifically, traits of Conscientiousness such as Competence (p=0.046), Dutifulness (p=0.043), Achievement-Oriented (p=0.050) and Self-Discipline (p=0.028) were associated with better Multiple Mini Interviews performance. Other domains, like Neuroticism, Extraversion, Openness, and Agreeableness, showed no significant correlation. Additionally, socio-demographic factors had no significant impact on performance. Conclusion The findings validate the Multiple Mini Interviews as an effective method for medical school selection, as they correlate with high-value personality traits such as Conscientiousness, while not favoring irrelevant individualities. These results orient the enhancement of selection methods, ensuring a diverse and competent student body and, overall, improving medical education. The findings thus support the use of structured interviews in admission processes, highlighting their role in identifying candidates with essential qualities for success in medical education and practice, and offer valuable insights for similar educational institutions aiming to refine their selection methods.